A systematic review of factors influencing spatiotemporal variability in urban water and energy consumption - Voskamp, Ilse M.; Sutton, Nora B.; Stremke, Sven; Rijnaarts, Huub H.M. (Journal of cleaner production, 2020)
Understanding which factors influence urban metabolism is a prerequisite for designing policies and plans that effectuate sustainable resource management. A growing number of publications is concerned with these factors. Yet, this emerging field of research lacks a common framework that supports researchers in interpreting their findings, such as generalizability to other cities, and making informed decisions on their research design. Aiming to contribute to building such a framework, we systematically reviewed urban metabolism literature. This review paper presents an overview of factors influencing urban water and energy consumption and their effect on consumption, and it describes the interconnectedness of these factors for six different types of relationships. Results disclose fourteen drivers, changes in societal context that shape consumption patterns, and twenty-one facilitators/constraints. The latter type of factors include consumer, resource and urban landscape characteristics that affect resource consumption by facilitating or constraining specific activities. Findings indicate commonalities between primary studies in terms of prevalent observed effect direction for a given factor. However, the interconnections between different factors can influence the direction and magnitude of effects and thereby result in case-specific variability in consumption patterns. Future research should enhance the understanding of these interconnections, strengthen the evidence for the factors presented here and provide insight in additional factors of influence. It is essential to align these studies in terms of a common terminology, transparent quality assessment and a unified approach to measuring and expressing factors of influence. Connecting with related disciplines working on a common systems approach is key to realize the full potential of urban metabolism research to advance our understanding of cities. •We present an overview of the factors influencing urban water and energy consumption.•Changes in societal context affect consumption as drivers.•Consumer, resource and urban landscape characteristics act as facilitator/constraint.•These factors are interconnected across various spatial and temporal scale levels.•This interconnectedness generates case-specific effects on consumption patterns.